(untitled) (Research, Society and Development, 2021)
Objective: Treponema denticola “T. denticola” is a pathogen associated with periodontal diseases that exhibits capacity for adherence, invasion, and colonization of host tissues, which allows alternating its location and damage in different sites of human body. This review aimed to discuss different studies that detected T. denticola in atherosclerotic plaques, demonstrating the importance of periodontal disease on the systemic health and the necessity of exploring the outcome of this colonization apart from the oral cavity. Methodology: Fifty-five studies were identified and gathered in this review according to the following topics: Periodontal disease, atherosclerosis and T. denticola. In vitro and in vivo studies published between 2002 and 2020 were searched on PubMed, raising relevant insights about the role of T. denticola and its association with the systemic disease, atherosclerosis, focusing on the bacterial tissue invasion and development of atherosclerosis. Results: After bibliographic review, it was possible to identify studies demonstrating the presence of T. denticola and other oral pathogens in cardiac or vascular tissues and in blood serum, as well, there is research in which other evidence of a relationship with atherosclerosis is shown. Conclusion: The invasion of periodontal pathogens and its toxins associated to the host’s immune and inflammatory response may contribute to the development of atherosclerosis.